Sperm motility in fishes: (III) diversity of regulatory signals from membrane to the axoneme - Alavi, Sayyed Mohammad Hadi; Cosson, Jacky; Bondarenko, Olga; Linhart, Otomar (Theriogenology, 2019)
Fish spermatozoa acquire potential for motility in the sperm duct where they are immotile. Osmolality of the seminal plasma is a key factor to maintain spermatozoa in the quiescent state in either freshwater or marine fishes. However, potassium (K+) ions prevent spermatozoa motility in salmonid and sturgeon fishes, while CO2 inhibits spermatozoa motility in flatfishes. Once, spermatozoa are released at spawning, their motility is initiated in hypo-osmotic and hyper-osmotic environments in freshwater and marine fishes, respectively. Some substances produced by the testes (a progestin), or released from oocytes (peptides) induce spermatozoa hypermotility in some marine fishes including the Atlantic croaker and Pacific herrings, respectively. Duration of spermatozoa motility is short, lasting for a few seconds to few minutes in most fishes due to rapid depletion of energy required for the beating of the motility apparatus called axoneme. In the osmotic-activated spermatozoa, K+ and water effluxes occur in freshwater and marine fishes, respectively, which trigger spermatozoa motility signaling. In general, initiation of axonemal beating is associated with an increase in intracellular calcium (Ca2+) ions in spermatozoa of both freshwater and marine fishes and a post- or pre-increase in intracellular pH, while cyclic adenosine monophosphate (cAMP) remains unchanged. However, axonemal beating is cAMP-dependent in demembranated spermatozoa of salmonid and sturgeon fishes. Calcium from extracellular environment or intracellular stores supply required Ca2+ concentration for axonemal beating. Several axonemal proteins have been so far identified in fishes that are activated by Ca2+ and cAMP, directly or mediated by protein kinase C and protein kinase A, respectively. The present study reviews differences and similarities in complex regulatory signals controlling spermatozoa motility initiation in fishes, and notes physiological mechanisms that await elucidation.
Keywords: signální transdukce; ATP; Sperm Motility; mužské pohlaví; Signal Transduction; Seminal plasma; cAMP; Ionic signaling; zvířata; Species Specificity; Osmolality; pH; motilita spermií; Fishes; druhová specificita; ryby; Spermatozoa; spermie; Male; Animals